2015
DOI: 10.1002/mnfr.201500373
|View full text |Cite
|
Sign up to set email alerts
|

Se-Allylselenocysteine induces autophagy by modulating the AMPK/mTOR signaling pathway and epigenetic regulation of PCDH17 in human colorectal adenocarcinoma cells

Abstract: These results reveal that ASC is an effective inducer of autophagy through regulating the AMPK/mTOR and PCDH17 expression via epigenetic modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 42 publications
3
31
0
Order By: Relevance
“…Interestingly, we also identified that AMPK signaling is responsible for NP-induced mTOR inhibition in SCs. AMPK has been shown to dephosphorylate TSC2, which inhibits mTOR activity and stimulates autophagy (Tanwar et al 2012;Wu et al 2015;Xu et al 2014). As in our study, specifically inducing activation of AMPK with AICAR further decreased the phosphorylation of TSC2 in NP-treated SCs, whereas pharmacological blockade and siRNA-mediated knockdown of AMPK inhibited it.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Interestingly, we also identified that AMPK signaling is responsible for NP-induced mTOR inhibition in SCs. AMPK has been shown to dephosphorylate TSC2, which inhibits mTOR activity and stimulates autophagy (Tanwar et al 2012;Wu et al 2015;Xu et al 2014). As in our study, specifically inducing activation of AMPK with AICAR further decreased the phosphorylation of TSC2 in NP-treated SCs, whereas pharmacological blockade and siRNA-mediated knockdown of AMPK inhibited it.…”
Section: Discussionsupporting
confidence: 78%
“…AMPK-regulated mTOR signaling pathway has been suggested to be one of the master regulators of autophagy (Wu et al 2015;Yamamoto et al 2014). We next investigated whether NP induces autophagy through modulation of AMPK-mTOR pathway in testis.…”
Section: Np Triggers Activation Of Ampkα-tsc2-mtor-p70s6k/4ebp1 Signamentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that PMFs increase TIMPs and decrease MMPs suggests that PMFs possess antimetastasis properties. In particular, protocadherins 17 (PCDH17) exhibited anticancer cell growth and antimetastasis activities by inducing PCD and regulating the cell cycle . In this study, we found that PMFs restored the substantially decreased PCDH17 level in the B a P/DSS‐induced tumorigenesis model.…”
Section: Resultsmentioning
confidence: 65%